2013
DOI: 10.1016/j.juro.2013.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Association of Microvascular and Capillary-Lymphatic Invasion with Outcome in Patients with Renal Cell Carcinoma

Abstract: Purpose We evaluated the association of microvascular invasion (MVI) and capillary-lymphatic invasion (CLI) with patient outcome following nephrectomy for renal cell carcinoma (RCC). Material and Methods We identified 1,433 patients surgically treated for sporadic, unilateral RCC between 2001 and 2008. All specimens were reviewed by a single uropathologist for MVI and CLI. Associations with time to metastases and death from RCC were evaluated using Cox proportional hazards models, controlling for established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Our current findings regarding KIM-1 in RCC contrast that of several groups who have claimed that KIM-1 promotes tumour growth and exacerbates cancer progression. Microvascular invasion (MVI) is defined by the invasion of cancer cells into the endothelial walls of small blood vessels and is associated with higher risks of metastases and death in patients with ccRCC 14 , 37 . Mijuskovic et al (2018) showed that high degrees of MVI were associated with significantly increased expression of tumour tissue KIM-1, and that urinary KIM-1 was associated with worse disease prognoses and higher TNM staging 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Our current findings regarding KIM-1 in RCC contrast that of several groups who have claimed that KIM-1 promotes tumour growth and exacerbates cancer progression. Microvascular invasion (MVI) is defined by the invasion of cancer cells into the endothelial walls of small blood vessels and is associated with higher risks of metastases and death in patients with ccRCC 14 , 37 . Mijuskovic et al (2018) showed that high degrees of MVI were associated with significantly increased expression of tumour tissue KIM-1, and that urinary KIM-1 was associated with worse disease prognoses and higher TNM staging 38 .…”
Section: Resultsmentioning
confidence: 99%
“…However, previously in 2013, a Mayo Clinic study assessed 119/1433 patients with MVI and observed an association with unfavorable prognostic characteristics, risk of metastasis and death from cancer in the univariate analysis, but in the multivariate analysis does not remain significant after being controlled with other prognostic variables established [27].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcomatoid component was defined as a spindle cell malignancy with the histological appearance of a sarcoma. Capillary-lymphatic invasion (CLI) was used to define tumors in microscopic capillary or lymphatic channels in lacking a muscular coat ( 15 ). All removed LNs were examined for the presence of nodal metastases.…”
Section: Methodsmentioning
confidence: 99%